A system for fruit grading & quality determination. - Mohamed Shariff, Abdul Rashid; Mahmud, Ahmad Rodzi; Mohd Shafri, Helmi Zulhaidi; Ben Saeed, Osama Mohamed; Amiruddin, Mohd Din (2010)

(untitled)
The present invention discloses an edible semi-solid/solid oil formulation from Canarium odontophyllum kernel oil (COKO) comprising 60.7% of saturated fatty acid (SFA), 36.5% of monosaturated fatty acid (MUFA) and 3.7 % of polyunsaturated fatty acid. The formulation in the present invention also contains polyphenolic compounds. COKO in the present invention is a potential source and starting ingredient for edible oil spreads, margarines, mayonnaises, shortenings, chocolates and cosmetic products. The present invention has also shown to excellently improve and maintain favorable plasma lipids profile (significantly lower TC, LDL-C and TG levels, significant increased in HDL-C level) and increased total antioxidant status. Therefore, COKO formulation is a potential edible semi-solid/solid oil spread or shortening, which also proven to improve plasma lipid profile and total antioxidant status.